2011
DOI: 10.1007/s11999-010-1605-0
|View full text |Cite
|
Sign up to set email alerts
|

Do Large Heads Enhance Stability and Restore Native Anatomy in Primary Total Hip Arthroplasty?

Abstract: Background Dislocation remains a serious complication in hip arthroplasty. Resurfacing proponents tout anatomic femoral head restoration as an advantage over total hip arthroplasty. However, advances in bearings have expanded prosthetic head options from traditional sizes of 22, 26, 28, and 32 mm to diameters as large as 60 mm. Large heads reportedly enhance stability owing to increased range of motion before impingement and increased jump distance to subluxation. Available larger diameter material combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
69
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 37 publications
(73 reference statements)
3
69
0
1
Order By: Relevance
“…However, limitations associated with polyethylene bearings such as wear, osteolysis, and late instability, in conjunction with advances in metallurgy, improved understanding of articulation mechanics, and implant manufacturer marketing bolstered the resurgence of MoM THA. In addition to the potential for obviating polyethylene-associated complications, MoM bearing surfaces allowed for larger head sizes, thereby affording increased ROM, reduced impingement, and lower dislocation rates [11,20,26,34]. Because of these apparent advantages, use of MoM implants increased, and by 2006, they accounted for more than one-third of the US market [9,36].…”
Section: Introductionmentioning
confidence: 99%
“…However, limitations associated with polyethylene bearings such as wear, osteolysis, and late instability, in conjunction with advances in metallurgy, improved understanding of articulation mechanics, and implant manufacturer marketing bolstered the resurgence of MoM THA. In addition to the potential for obviating polyethylene-associated complications, MoM bearing surfaces allowed for larger head sizes, thereby affording increased ROM, reduced impingement, and lower dislocation rates [11,20,26,34]. Because of these apparent advantages, use of MoM implants increased, and by 2006, they accounted for more than one-third of the US market [9,36].…”
Section: Introductionmentioning
confidence: 99%
“…MOM articulations allow for larger head-neck ratios than current options for MOP, which allows for a larger ROM before impingement and stability [31]. Recent studies demonstrated largerdiameter metal heads decreased dislocation rates to as low as 0.05% and were able to better approximate anatomic femoral heads in primary arthroplasty [21], while other studies found a higher rate of revision for dislocation, up to 0.8% in hard-on-hard THA, particularly with the use of smaller head sizes [26].…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of new materials designed to reduce wear (crosslinked polyethylene) [8,13,21] and hard bearings to reduce wear and frictional torque (ceramic-on-ceramic, metal-on-metal) [11,17,18,22], the number of THAs with larger diameter heads has increased in recent years. Larger heads may offer distinct advantages, including reduced risk of dislocation and component impingement, as well as increased ROM in some cases [1,6,10,15,20]. Furthermore, larger femoral heads have been theorized to improve joint biomechanics and perhaps better approximate a more normal-feeling hip [10].…”
Section: Introductionmentioning
confidence: 99%
“…Larger heads may offer distinct advantages, including reduced risk of dislocation and component impingement, as well as increased ROM in some cases [1,6,10,15,20]. Furthermore, larger femoral heads have been theorized to improve joint biomechanics and perhaps better approximate a more normal-feeling hip [10].…”
Section: Introductionmentioning
confidence: 99%